2022
DOI: 10.3390/jcm11185268
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Domperidone in Combination with Proton Pump Inhibitors in Gastroesophageal Reflux Disease: A Systematic Review and Meta-Analysis of Randomised Controlled Trials

Abstract: The aims of gastroesophageal reflux disease (GERD) treatment are symptom relief and healing of oesophagitis. Besides proton pump inhibitors (PPIs), prokinetic agents are also commonly prescribed to treat GERD. Domperidone, a well-known antiemetic, is an example of a prokinetic agent. It is a dopaminergic blocker that increases lower oesophagus sphincter pressure and activates gastric motility. We carried out a systematic review and meta-analysis to explore the benefits of domperidone in addition to PPI therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…Prior studies presented same results to our study. [16,17] [18], a reduced cardiovascular risk, and fewer SEs. In patients with gastroparesis, domperidone and erythromycin both improved the symptom score more than other prokinetics.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies presented same results to our study. [16,17] [18], a reduced cardiovascular risk, and fewer SEs. In patients with gastroparesis, domperidone and erythromycin both improved the symptom score more than other prokinetics.…”
Section: Discussionmentioning
confidence: 99%
“…Promotes gastric peristalsis and emptying, in addition to inhibiting reflux of gastric contents after meals; can increase pressure on the lower oesophageal sphincter [41,90,91] Sulpiride DRD2 inhibitor Can reduce the secretion of gastric protein and gastric acid and inhibit the development of gastric ulcers [18,35,42] Cisapride DRD2 antagonist Can increase the release of acetylcholine in the intestinal plexus to stimulate the movement of the lower oesophagus, stomach, and small intestine [19] SKF 38393 DRD1 inhibitor Inhibits the development of gastroduodenal ulcers [35] Metoclopramide DR antagonist Increases gastric emptying while also exerting antiemetic effects [39,40] Domperidone DRD2 antagonist Inhibits intestinal motility, regulates sodium absorption and mucosal blood flow, and has a protective effect against gastroduodenal ulcers [47,48] Calilazine DRD3 antagonist Can inhibit multiple drug resistance and make colon and lung cancer cells sensitive to antitumor drugs [52] Pimozite DRD2 antagonist Inhibits the growth and metastasis of colorectal cancer (CRC) [53] Thioridazine DRD2 antagonist Inhibits the growth of gastric cancer cells to exert antitumor effects; ameliorates hepatocellular carcinoma to possibly reduce the risk of tumour metastasis [54,83] Quinpirol DRD2 agonist Reduces the permeability of blood vessels and prevents excessive leakage of blood vessels, thereby decreasing the severity of UC [56,57,62] Bromocriptine…”
Section: Domperidone Drd2 Antagonistmentioning
confidence: 99%
“…No significant difference was demonstrated in symptomatic improvement between placebo, domperidone, and metoclopramide 259 . A recent meta‐analysis analyzed the beneficial effect of domperidone in addition to PPI therapy for GERD and showed that combination of a PPI and domperidone significantly reduced global GERD symptoms compared to PPI monotherapy, with a significant decrease in GERD scores (OR: −0.72, 95% CI: −0.95–[−0.48], p < 0.0001) and heartburn scores (OR: −1.73, 95% CI: −2.67–[−0.78], p < 0.0001) 260 …”
Section: Dopamine‐2 Receptor Antagonistsmentioning
confidence: 99%